The full recovery of mice (Mus Musculus C57BL/6 strain) from virus-induced sarcoma after treatment with a complex of DDMC delivery system and sncRNAs - Klimenko, Oxana V; Sidorov, Alexey (Non-coding RNA research, 2019)
BACKGROUND: Virus-induced cellular genetic modifications result in the development of many human cancers. METHODS: In our experiments, we used the RVP3 cell line, which produce primary mouse virus-induced sarcoma in 100% of cases. Inbreed 4-week-old female C57BL/6 mice were injected subcutaneously in the interscapular region with RVP3 cells. Three groups of mice were used. For treatment, one and/or two intravenous injections of a complex of small non-coding RNAs (sncRNAs) a-miR-155, piR-30074, and miR-125b with a 2-diethylaminoethyl-dextran methyl methacrylate copolymer (DDMC) delivery system were used. The first group consisted of untreated animals (control). The second group was treated with one injection of complex DDMC/sncRNAs (1st group). The third group was treated with two injections of complex DDMC/sncRNAs (2nd group). The tumors were removed aseptically, freed of necrotic material, and used with spleen and lungs for subsequent RT-PCR and immunofluorescence experiments, or stained with Leishman-Romanowski dye. RESULTS: As a result, the mice fully recovered from virus-induced sarcoma after two treatments with a complex including the DDMC vector and a-miR-155, piR-30074, and miR-125b. In vitro studies showed genetic and morphological transformations of murine cancer cells after the injections. CONCLUSIONS: Treatment of virus-induced sarcoma of mice with a-miR-155, piR-30074, and miR-125b as active component of anti-cancer complex and DDMC vector as delivery system due to epigenetic-regulated transformation of cancer cells into cells with non-cancerous physiology and morphology and full recovery of disease.
Keywords: Mice; Src tyrosine kinase; Small non-coding RNAs; Epigenetic therapy; Sarcoma; DDMC vector